2022
DOI: 10.3390/su14137981
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Inhibition Evaluation of Chitosan–CuO Nanocomposite for Carbon Steel in 5% HCl Solution and Effect of KI Addition

Abstract: Chitosan–copper oxide (CHT–CuO) nanocomposite was made by an in-situ method utilizing olive leaf extract (OLE) as reductant. The OLE mediated CHT–CuO nanocomposite containing varying amount of chitosan (0.5, 1.0 and 2.0 g) was evaluated as corrosion inhibitor for X60 carbon steel in 5 wt% hydrochloric acid solution. The corrosion inhibitive performance was assessed utilizing weight loss and electrochemical impedance spectroscopy, linear polarization resistance and potentiodynamic polarization techniques comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Ongoing research delves into developing and applying these green corrosion inhibitors, simultaneously mitigating corrosion-related issues, while minimizing environmental harm, which appears increasingly promising, heralding a more sustainable future for corrosion protection. By repurposing waste substances such as agricultural byproducts, discarded plant matter, and industrial residues, 544,545 researchers aim to create effective corrosion inhibitors that efficiently protect metals and alloys and contribute to waste reduction and resource optimization. Research indicates that household-generated food waste comprised of fresh fruits and vegetables accounts for nearly half of this type of waste.…”
Section: Green Corrosion Inhibition Using Waste Materials (Economy)mentioning
confidence: 99%
See 1 more Smart Citation
“…Ongoing research delves into developing and applying these green corrosion inhibitors, simultaneously mitigating corrosion-related issues, while minimizing environmental harm, which appears increasingly promising, heralding a more sustainable future for corrosion protection. By repurposing waste substances such as agricultural byproducts, discarded plant matter, and industrial residues, 544,545 researchers aim to create effective corrosion inhibitors that efficiently protect metals and alloys and contribute to waste reduction and resource optimization. Research indicates that household-generated food waste comprised of fresh fruits and vegetables accounts for nearly half of this type of waste.…”
Section: Green Corrosion Inhibition Using Waste Materials (Economy)mentioning
confidence: 99%
“…The highest observed inhibition efficiency (IE%) was 99.91% at a 100 ppm concentration of the TiO 2 ·B 2 O 3 -[TBID] inhibitor in an acidic medium. In a separate investigation, 544 researchers examined the efficacy of an olive leaf extract-mediated chitosan (CHT)–CuO nanocomposite as a corrosion inhibitor for X60 carbon steel exposed to a 5% HCl solution. The corrosion inhibition performance displayed the following trend: CHT1.0–CuO nanocomposite (90.35%) exhibited a superior performance compared to CHT0.5–CuO (90.16%) and CHT2.0–CuO (89.52%).…”
Section: Green Corrosion Inhibition: Current Advancements and Future ...mentioning
confidence: 99%
“…The rate was however observed to increases with increase in temperature and peaked at 323 K. The highest corrosion rate was observed for the blank at 323 K. The observed increase in corrosion inhibition efficiency with increasing temperature (303 to 323 K) has been explained to be due to an increase in the medium's corrosive activity as a result of an increase in the thermal agitation of its molecules and an increase in its conductivity. 4 It was also explained that the decrease in the inhibition efficiency at 333 K might be due to the desorption of the adsorbed inhibitor on the metal's surface due to increased thermal agitation. Also, the increasing inhibition efficiency with increasing concentration could be linked to the increasing surface coverage of the metal with increasing concentration.…”
Section: Corrosion Inhibition Studiesmentioning
confidence: 99%
“…Green inhibitors are sourced majorly from various parts of plants including the roots, fruits, leaves and oils of plants 1 and sometimes could be hybrid materials such as chitosan-CuO nanocomposite, which has been used in corrosion protection of steel in acidic medium. 4 Ag-CuO/epoxy hybrid nanocomposite has also been applied as green coating to prevent corrosion of copper. 5 The efficiency of plants extracts from mango and orange peels, garlic peels, castor bean, coffee powder, white tea, etc as green inhibitors of carbon steel in acidic medium was recently further demonstrated in a recent survey demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, according to John et al [21], a chitosan-ZnO nanocomposite may provide 73.80% protection to mild steel surfaces in 0.1 N HCl solution, compared to 32.47% protection provided by chitosan alone. It has been reported that an olive leaf extract-mediated chitosan-CuO nanocomposite with different amounts of chitosan (0.5, 1.0, and 2.0 g) was tested as a CI for X60 CS in a 5% HCl solution [22]. It was found that the corrosion protection performance was in the order CHT 1.0 -CuO (90.35%) > CHT 0.5 -CuO (90.16%) > CHT 2.0 -CuO (89.52%) nanocomposite from impedance measurements.…”
Section: Introductionmentioning
confidence: 99%